Infants Investigated by the Child Welfare System: Exploring a Distinct Profile of Risks, Service Needs, and Referrals for Support in Ontario - Joanne Filippelli; Barbara Fallon; Esme Fuller-Thomson; Nico Trocmé (Brain Sciences, 2017)
The science of early childhood development underscores that maltreatment and other adversities experienced during infancy heightens the risk for poor developmental and socio-emotional outcomes. Referrals to supportive services by the child welfare system are particularly critical during infancy given the rapidity of brain development and infants’ sensitivity to their environment. The main objectives of the current study are to: (1) examine age-specific differences in clinical and case characteristics; (2) determine the factors associated with the service referral decision involving infants; and (3) explore the types of services families have been referred to at the conclusion of a maltreatment-related investigation. Using data from the Ontario Incidence Study of Reported Child Abuse and Neglect for 2013, descriptive analyses were conducted, as was a logistic regression to identify factors associated with the decision to refer families of infants to supportive services. Overall, the findings reveal that the profile of infants and their families differs distinctly from those of older children with respect to risks, service needs, and service referrals, although this is rarely reflected in child welfare practice and policy. Investigations involving infants were most likely to have a referral made to supportive services, least likely to have an infant functioning concern identified; most likely to have a primary caregiver risk factor identified; and, the greatest likelihood of experiencing economic hardship. Multiple risks, identified for the primary caregiver of the infant are correlated to referral decisions for infants. However, the needs of the infant are likely under-identified and require cross-sectorial collaboration.